Pomodoro Technique illustrated : the easy way to do more in less time - Nöteberg, Staffan (Pragmatic life., 2009)
Originally developed by Francesco Cirillo, the Pomodoro technique will help you work in focused sprints throughout the day. It shows you how to organize your work to accomplish more in less time. You don't need for expensive software or fancy planners. You can get started with nothing more than paper, a pencil, and a kitchen timer.--Publisher.